Pengaruh Penempatan Kerja, Mutasi dan Beban Kerja terhadap Kinerja Karyawan pada PT PLN (Persero) Unit Induk Distribusi Aceh - Iqbal Aulia Rahman, Muhammad; Suryani Murad; Nadiya Nadiya (Jurnal Sains dan Ilmu Terapan, 2025)
This study aims to analyze the influence of job placement, transfer, and workload on employee performance at PT. PLN (Persero) Aceh Distribution Unit. This study uses a census method, in which all elements of the population totaling 96 employees are directly investigated. Data were collected through questionnaires distributed to employees, using a Likert scale to measure the variables of job placement, transfer, workload, and employee performance. The results of the regression analysis indicate that partially, job placement, transfer, and workload have a significant influence on employee performance. Appropriate job placement can increase motivation and work efficiency, while transfers carried out by considering individual abilities have a positive impact on adaptation and productivity. A balanced workload also plays an important role in reducing work stress and improving performance. In addition, simultaneous analysis using the F test shows that the three variables together have a significant influence on employee performance.